Pengaruh Kualitas Pelayanan, Harga dan Lokasi Terhadap Keputusan Menginap - Montel Sinaga; Dewi Shinta Wulandari Lubis (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Service quality is very important in the development of a hotel, namely to attract guests who come and become regular visitors, as well as price and location. Price and location is one of the keys to the success of a business, especially in the hospitality sector. Currently every hotel has the goal of ensuring an adequate level of profitability from its core activities, which can be achieved not only by reducing the cost of providing hotel services, but also by setting an optimal price for their services. and the location at the Hotel Pansur Gading Ressort. The respondents of this study were 20% of all hotel guests, namely 40 people. This research method used SPSS 25, the data analysis method was descriptive quantitative, and this study used multiple linear regression analysis mode. The results of this study explain that the better the quality of service, price and location, the higher the level of visitors. Partially, the service quality and price variables of this study have no effect on the dependent variable And Resort. However, the location variable has a positive and significant effect on the purchasing decisions of visitors at Pancur Gading Hotel And Resort.